Rapid and easy determination of morphine in chafing dish condiments with colloidal gold labeling based lateral flow strips - Wei Chen; Xin-ni Li; Qian Wu; Li Yao; Jianguo Xu (Food Science and Human Wellness)
In order to enhance the flavor of chafing dish and increase the attraction of consumers, the poppy shell is reported to be illegally added to the condiments of chafing dish. In this research, a rapid, simple, and convenient method based on the classic immunochromatographic lateral flow strip (LFS) with gold nanoparticles (GNPs) labeling was developed for easy monitoring of morphine (MOP), an effective component of poppy shell. Under optimized conditions, this developed LFS can well realize the detection of target MOP in the condiments of chafing dish in less than 10 min without any complicated pre-treatments. The limit of detection (LOD) can be achieved as low as 0.1 ppb for standard MOP or the MOP spiked condiments of chafing dish. All these results of the research strongly demonstrate that this established LFS method can be successfully applied in practical rapid and accurate on-site screening of poppy shell in condiments of chafing dish. Keywords: Morphine (MOP), Gold nanoparticles (GNPs), Lateral flow strip (LFS), Chafing dish condiments